Rethinking relief, reconstruction and development: Evaluating the effectiveness and sustainability of post-disaster livelihood aid. (October 2020) - Daly, Patrick; Mahdi, Saiful; McCaughey, Jamie; Mundzir, Ibnu; Halim, Agus; Nizamuddin,; Ardiansyah,; Srimulyani, Eka
Abstract: This paper presents a field study on the long-term effectiveness and sustainability of livelihood interventions following the 2004 Indian Ocean tsunami in Aceh, Indonesia. We assess the extent to which post-tsunami aid in Aceh helped beneficiaries to stabilize and restore their pre-disaster livelihoods, and/or develop new livelihoods. We draw upon qualitative data captured in 183 in-depth interviews and 38 focus group discussions involving village leaders, livelihood aid participants, and NGO workers. Our results show that livelihood assistance helped people stabilize their household finances and partially restore their pre-disaster livelihoods. Furthermore, we found that aid programs were able to help some people without pre-disaster livelihood experience to participate in part-time, ad hoc work. However, aid packages were generally not able to support the development of full-time, sustainable new livelihoods for people lacking pre-disaster training and experience. Our data suggests that it is difficult to conduct efficient and sustainable livelihood development initiatives within the time pressures and current institutional approaches to large-scale post-disaster reconstruction.